(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2017)
The behavior of 2-pyrimidinylacetonitriles, such as 2-(4,6-dimethyl-2-pyrimidinyl)acetonitrile and 2-(2,6-dimethyl-4-pyrimidinyl)acetonitrile in Houben-Hoesch reaction was investigated. It was found that the result of the reaction depends on the structure of the starting nitrile. The reaction of 2-(4,6-dimethyl-2-pyrimidinyl)acetonitrile and resorcinol or 4-ethylresorcinol in BF3*Et2O with hydrogen chloride, followed by hydrolysis resulted in α-(4,6-dimethyl-2-pyrimidinyl)-2,4-dihydroxyacetophenones, while 2-(2,6-dimethyl-4-pyrimidinyl)acetonitrile in this reaction failed to give α-(2,6- dimethyl-4-pyrimidinyl)-2,4-dihydroxyacetophenone because of the pyrimidine ring-opening. The interaction of α-(4,6-dimethyl-2-pyrimidinyl)-2,4-dihydroxyacetophenones with chloroacetyl chloride in acetonitrile in the presence of pyridine was investigated. α-(4,6-Dimethyl-2-pyrimidinyl)-2,4-dihydroxyacetophenones underwent acylation with chloroacetyl chloride, followed by cyclization to give 2-chloromethyl-7-chloroacetoxy-3-(4,6-dimethyl-2-pyrimidinyl)-4H-4-chromenones, which can undergo subsequent intramolecular cyclization with annelation of pyrrolopyrimidine ring to chromone core. A result of this reaction starting from α-(4,6-dimethyl-2-pyrimidinyl)-2,4-dihydroxyacetophenone is 2,4-dimethyl-12-oxo-12Н-chromeno[3’,2’:3,4]pyrrolo[1,2-a]pyrimidin-9-yl 2-chloroacetate, which is the derivative of the new heterocyclic system 12H-chromeno[3’,2’:3,4]pyrrolo[1,2-a]pyrimidin-12-one.